HUBUNGAN FAKTOR INDIVIDU DAN FAKTOR ORGANISASI DENGAN PERILAKU AMAN PADA PEKERJA BAGIAN PRODUKSI PT X TAHUN 2023 - Theophoebe Abigail Geraldine Surbakti (2023)
Production workers are at major risk because they had direct contact with machinery, equipment and hazard exposure. This risk can increase and cause occupational accidents if workers do not behave safely while working. Occupational accidents caused workers to lose their working days and risk hampering production activities. This study aims to determine the relationship between individual factors and organizational factors with the safe behaviour of PT X production workers. This study used a cross-sectional study design with a population of 120 workers and 100 workers as a sample with purposive sampling techniques. Data collection used a modified questionnaire from previous research and has been tested for validity and reliability. The analysis of chi-square results showed a significant relationship between age, length of service, knowledge, and management commitment and safe behaviours. There was no relationship between education, attitudes, work regulations and procedures and communication with safe behaviour. It is suggested that PT X provide safety training and additional education through programs or socialization, impose strict sanctions and provide rewards as motivation, and increase the number of supervisors. For workers to comply with regulations and procedures and participate in safety programs, and report work accidents.